The Agroecological Systems of the San Lucas Parish (Loja). Resilient Practices in the Face of Climate Change - Coronel Alulima, Tatiana Nathalí (2019)
The forecasts of international organizations on the effects of climate change are not encouraging, let alone for small producers. This article aims to analyze the resilience of agroecological production systems in San Lucas against this reality, as well as their contribution to the food sovereignty of the population. The investigation is carried out in three grassroots organizations of the Loja Agroecological Network, in which resilience indicators are evaluated based on three dimensions of analysis: farmers' perception of climate change, vulnerability measurement, and responsiveness and recovery. From the latter, the criterion of food sovereignty for an individual analysis is extracted, due to the relevance of its contribution within the analyzed theme. When assessing the response and recovery capacity, it is concluded that the parish's agroecological systems present a vulnerability that ranges from medium to low. Therefore, it is necessary to improve parameters such as vegetation cover, riverine forest conservation, and type of irrigation. In relation to food sovereignty, the research identifies that the food system is based primarily on ancestral customs. Even with limitations, agroecological production systems are a resilient alternative to climate change, due to the productive, cultural and organizational characteristics found in the study.